Nilai-nilai Pendidikan Akhlak dalam YouTube Syamil Dodo Tema Alam Kubur Episode 3 - Yulia Rahmawati; Indah Muliati (Prodi Pendidikan Keagamaan Islam, 2022)
One of the crucial causes of moral decadence is the lack of inculcating the values ​​of moral education in children from an early age. Therefore, the role of parents is very important in shaping children's noble character, by accompanying and facilitating children's learning activities. Children's learning activities also develop with the presence of shows through the YouTube application, Syamil Dodo's YouTube channel can be used as an alternative in instilling the value of moral education in early childhood. This study aims to: analyze the values ​​of moral education for early childhood in Syamil Dodo's YouTube videos the theme of the grave nature of episode 3. The method used is a descriptive method, with the type of documentary analysis. The results of this study indicate that there are five values ​​of moral education contained in Syamil Dodo's YouTube video with the theme of the grave in episode 3, namely 1) believing in the angels Munkar and Nakir, 2) worshiping Allah SWT, 3) believing in and following the teachings of the Prophet Muhammad, 4 ) maintain self-sanctity, 5) be obedient and obedient to parents.